A new synthetic antitumor naphthoquinone induces ROS-mediated apoptosis with activation of the JNK and p38 signaling pathways. (1st July 2021) - de Almeida, Patricia D.O.; dos Santos Barbosa Jobim, Gleyce; dos Santos Ferreira, Caio César; Rocha Bernardes, Lucas; Dias, Rosane B.; Schlaepfer Sales, Caroline B.; Valverde, Ludmila de F.; Rocha, Clarissa A.G.; Soares, Milena B.P.; Bezerra, Daniel P.; de Carvalho da Silva, Fernando; Cardoso, Mariana Filomena do Carmo; et al.
Abstract: Quinones are plant-derived secondary metabolites that present diverse pharmacological properties, including antibacterial, antifungal, antiviral, anti-inflammatory, antipyretic and anticancer activities. In the present study, we evaluated the cytotoxic effect of a new naphthoquinone 6b, 7-dihydro-5H-cyclopenta [ b ]naphtho [2, 1-d]furan-5, 6 (9aH)-dione) (CNFD) in different tumor cell lines. CNFD displayed cytotoxic activity against different tumor cell lines, especially in MCF-7 human breast adenocarcinoma cells, which showed IC50 values of 3.06 and 0.98 μM for 24 and 48 h incubation, respectively. In wound-healing migration assays, CNFD promoted inhibition of cell migration. We have found typical hallmarks of apoptosis, such as cell shrinkage, chromatin condensation, phosphatidylserine exposure, increase of caspases-9 and-3 activation, increase of internucleosomal DNA fragmentation without affecting the cell membrane permeabilization, increase of ROS production, and loss of mitochondrial membrane potential induced by CNFD. Moreover, gene expression experiments indicated that CNFD increased the expression of the genes CDKN1A, FOS, MAX, and RAC1 and decreased the levels of mRNA transcripts of several genes, including CCND1, CDK2, SOS1, RHOA, GRB2, EGFR and KRAS. The CNFD treatment of MCF-7 cells induced the phosphorylation of c-jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinases (MAPKs) and inactivation of extracellular signal-regulated protein kinase 1/2 (ERK1/2). In a study using melanoma cells in a murine model in vivo, CNFD induced a potent anti-tumor activity. Herein, we describe, for the first time, the cytotoxicity and anti-tumor activity of CNFD and sequential mechanisms of apoptosis in MCF-7 cells. CNFD seems to be a promising candidate for anti-tumor therapy. Highlights: A new anti-tumor naphthoquinone (CNFD) are strongly cytotoxic and induces apoptosis. The cytotoxicity can be mediated by an increase of ROS production. CNFD cause loss of mitochondrial membrane potential and activation of caspases. CNFD decrease B16F10 tumor in mice.